PENDEKATAN REKONSTRUKSI SOSIAL DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - ASMIN MAHDI; SABARUDIN SABARUDIN; GUSMA AFRIANI (Raudhah - Proud To Be Professional, 2022)
Abstract Education which basically aims to change life for the better sometimes has not been able to answer the problems that occur in society, this is due to the asymmetry between studies in the world of education and what is happening in the life of the surrounding community, especially when looking at the diversity of ethnicity, race, religion, languages as well as geographical conditions and different natural resources. esponding to this problem, the Social Reconstruction curriculum emphasizes the importance of the curriculum as a tool for reconstructing or rearranging people's lifestyles and culture. the social reconstruction approach departs from the problems faced in society as the contents of Islamic Religious Education, education can instill good values in people's lives, the function of the curriculum can carry out community and cultural renewal. Education graduates will be able to build new values in society as an absolute requirement which is the target of the curriculum. The results of this study, the authors analyze the social reconstruction curriculum development approach of Islamic Religious Education with the concept of learning Edu-Sosio-Spiritual. In carrying out this research study, the authors used the Library Research method and made books, journals, articles and other sources relevant to this research to analyze and find the core concept of social reconstruction education of Islamic Religious Education in rearranging the curriculum and concept of Islamic Religious Education that can useful and have an impact on people's lives.